Design and fabrication of monolithically integrated metalens for higher effective fill factor in long-wave infrared detectors. (March 2022) - Hou, Huwang; Zhang, Yiyuan; Luo, Zhendong; Zhang, Peng; Zhao, Yang
Highlights: The integration of long-wave infrared detector with micro-metalens is proposed. A polarization-independent and wide-band metalens is designed to use as the light concentrator. The fabrication process of the metalens that is compatible with general MEMS process is developed. The focusing effect of the designed metalens has been demonstrated successively. Abstract: Infrared imaging technology has been a worldwide research focus with various significant applications in the military and surveillance fields. Due to the complicated structure of the infrared imaging element, the photosensitive area only occupies quite a small part of each element, resulting in a low fill factor and thus limited utilization efficiency of incident light. By integrating a polarization-independent, wide-band focusing metalens into the imaging element of the long-wave infrared detector, the effective fill factor can be significantly improved. The monochromatic focusing efficiency of the metalens is up to 86%, and the average focusing efficiency in the wide spectral from 8 µm to 14 µm reaches 80%. The focusing measurement results demonstrate that the fabricated metalens can be used as a light concentrator to improve the detection sensitivity. The micro-optical metalens is flat and ultra-thin shaped, which is composed of sub-wavelength silicon pillars. Due to its compatibility with the detector manufacturing process, the metalens can be scaled up for a large micro-metalens array monolithically integrated with an infrared focal plane array(FPA).